Driver adaptation to information and assistance systems - Stevens, A. (Researcher in transportation).; Brusque, Corinne; Krems, Josef (Josef F.). (London, United Kingdom The Institution of Engineering and Technology, 2014)
The book comprises 17 chapters and discusses the following topics: driver adaptation; information and assistance systems, ADAPTATION Project; behavioural adaptation; ADAS; driver information processing and situation awareness; adaptive cruise control; intelligent driver support system; learning and aging; safety issues; intersection assistance system; mobile phone use; road safety; workload based driving assistance systems; distraction and inattention prevention; forward collision warning system; cognitive analysis; behavioural and electrophysiological measurements; automated platooning in traffic; user-centred design; driving simulators; and database development for behavioural data storage and analysis.
Electronic reproduction.
Keywords: Driver assistance systems; Motor vehicles -- Technological innovations; Motor vehicle drivers -- Attitudes; Motor vehicle driving; Analysis; Data processing; Database management; Electric alarms; Electronic alarm systems; Electrophysiology; Mobile communication systems; User-centered system design; Electronic books